Biossensor baseado em peptídeo mimético ligante de imunoglobulina G: uma plataforma para diagnóstico de artrite idiopática juvenil - Rodovalho, Vinícius de Rezende (2016)
Juvenile idiopathic arthritis (JIA) is a wide group of autoimmune and inflammatory diseases that affect children and adolescents under the age of sixteen. In the absence of proper diagnosis and treatment, irreversible damage may occur in the joint tissues. Biosensors emerge in the clinical scenario as promising analytical alternatives to the molecular diagnosis. In this work, an electrochemical biosensor was developed for the diagnosis of JIA using PRF+1 peptide, which has been shown to react against antibody from patients with JIA. The screenprinted electrode surface was activated by chronoamperometry prior to immobilization of the peptide. Electrochemical detections were conducted by differential pulse voltammetry and electrochemical impedance spectroscopy in phosphate buffer and/or potassium ferro/ferricyanide solution. Morphological alterations in the surfaces were studied by atomic force microscopy. The performance of the biosensor was evaluated by testing different serum specimen in different dilutions and stability during storage. The developed biosensor was able to discriminate samples of patients who were diagnosed as having JIA from those that were obtained from healthy individuals. The system presented linear range of response between the dilutions 1:25 and 1:300, sensitivity of 172,8 μC x DF, and limits of detection and quantification of 1:784 and 1:235, respectively. Moreover, the biosensor remained functional for up to 40 days of storage at 8°C. Therefore, a simple, miniaturized, functional, stable, selective and sensitive platform was developed and established as a promising strategy for molecular diagnosis.